Strategi Menghidupkan dan Meramaikan Musholla Darussalam, Jorong Situjuah Gadang, Nagari Situjuah Gadang - Zul Efendi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study formulates integrative strategies to revitalize the Darussalam Prayer Hall in Jorong Situjuah Gadang, Nagari Situjuah Gadang. A qualitative-descriptive case study was conducted using semi-structured interviews, participatory observation, and visual documentation, with data analyzed through reduction, thematic presentation, and triangulation. Results show a 25% increase in congregational attendance after improvements to physical facilities, particularly lighting and seating, accompanied by creative programs such as calligraphy, hadroh, and thematic studies. The use of local social media (WhatsApp and Instagram) enhanced digital engagement by 200%, while youth involvement grew significantly. Collaboration between takmir, community leaders, and digital volunteers was identified as a critical success factor. The study concludes that combining physical improvements, innovative programs, and digital communication creates a synergistic effect in revitalizing prayer hall activities. Recommendations include establishing an annual Islamic cultural festival, developing a digital scheduling platform, and strengthening takmir management training to ensure sustainability.